PENGARUH MODEL PEMBELAJARAN CORE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 34 PADANG - Surry, Salsa Billa (Jurnal Edukasi dan Penelitian Matematika, 2023)
The ability in mathematics that must be possessed includes skills in solving problems. Students in class VIII SMP Negeri 34 Padang still cannot achieve optimal mathematical problem solving skills. In order for this problem to be resolved, one effort that can be attempted is to apply the Connecting, Organizing, Reflecting, and Extending (CORE) learning model. This study intends to compare the effectiveness of the CORE model and the direct learning model in maximizing mathematical problem solving abilities. This study used a quasi-experimental type and nonequivalent posttest only control group design. The research that will be examined has a population of class VIII SMP Negeri 34 Padang in the 2022/2023 academic year. The research sample was obtained through simple random sampling by drawing lots. The instrument used in the research is the final test of mathematical problem solving ability, which intends to test the research hypothesis. Based on the results of the hypothesis test with a significant level / α = 0.05, a P-value = 0.000 is obtained which is <0.05 so that H0 is rejected. This indicates that the mathematical problem solving abilities of students who learn by applying the CORE model are superior compared to those who learn by direct learning model. This finding shows that students who use the CORE learning model have superior abilities in solving mathematical problems compared to students who use the direct learning model. Keywords – Connecting, Organizing, Reflecting, and Extending (CORE) Learning Models, Mathematical Problem Solving Ability, Direct Learning Models.